Students’ Mathematical Representation Ability Assessment Instrument Development in the Three-Dimensional Topics on the 12th grade of Senior High School - Hardy, Nabilla; Armis, Armis; Saragih, Sehatta (Journal of Educational Sciences, 2024)
The fact that students' mathematical representation abilities are still relatively low is an issue that continues to this day in the education sector. One of the factors that influence this issue is the lack of evaluation and habituation of students in solving mathematical problems that facilitate mathematical representation abilities. Good instruments certainly need to support these evaluation and habituation efforts. This research aims to produce an instrument for assessing students' mathematical representation abilities that meets criteria that are valid, reliable, have a good discriminatory item value, and good level of difficulty. This development research uses the Borg and Gall development model, which is carried out up to the main fields testing stage. From the research results, a set of instruments for assessing representational ability in Three - Dimensional topic which amounted to 15 questions, with 8 questions in Question Package 1 and 7 questions in Question Package 2, which met the criteria for validity, reliability, and have a good discriminatory item value with a good level of difficulty too. The instrument for assessing students' mathematical representation abilities was developed from these results and met with good final results.